PENGEMBANGAN MEDIA POWTOON TERHADAP KEMATANGAN KARIER SISWA KELAS X - Rahman, Isfira Reina; Mustika, Ika; Rismawati Siddik, Riesa (IKIP Siliwangi, 2023)
This study has the aim of developing a powtoon media on student career maturity. In this study using the Research and Development (R&D) method using a model from Brog and Gall. The subjects in this study were students of class X. The results of the study were 1. Product development stage a) Phase I Preliminary study. b) Phase II includes product design, product validation, product revision, product testing. 2. The eligibility of material experts, media experts, and practitioners gets a score in the